Análisis de calidad del servicio al cliente interno y externo para propuesta de modelo de gestión de calidad en una empresa de seguros de Guayaquil - Abad Acosta, María Gabriela (2014)
The current research report examines the quality of service provided to internal and external users of an insurance company in Guayaquil city. The overall objective of this work is to formulate a quality management model that analyze the level of satisfaction perceived by employees and insurance agents, and which would measure the level of attention provided, staff efficiency, speed of processes, and the incidence of these factors in the profitability of the organization. The need to investigate this study was due some evident problems that are reflected in the annual sales budget, which present a steady decline and important threat to the future of the organization. The research methodology was inductive – analytic because after the observation of the facts it was possible to collect information through the survey technique, which will help to establish the relationship between the internal customers’ expectations about the service, and what they actually received. The sample for this study was composed of 80 employees that were chosen randomly, and for the external customers, a sample with the 10 most relevant insurance agents was considered. The results showed the strengths and weaknesses of the referred institution and helped to identify the gaps in the quality of the service as well as in the organizational culture.